2020
DOI: 10.1042/bsr20193692
|View full text |Cite
|
Sign up to set email alerts
|

The association between dietary protein intake and esophageal cancer risk: a meta-analysis

Abstract: Correspondence: Hua Wang (wang hua@yeah.net) Several papers studied dietary protein intake as a potential influence factor for esophageal cancer, but their findings were inconsistent. Thus, this meta-analysis was performed to identify the effect of protein intake on esophageal cancer risk. Potential case-control studies or cohort studies from the databases of Embase, Web of Science and PubMed were searched. The strength of association was quantified by pooling odds ratio (OR) and 95% confidence interval (CI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We found that 42 (72.4%) meta-analyses included only prospective cohort studies, while 16 (27.6%) meta-analyses included either caseecontrol/cross-sectional studies or a combination of prospective cohort studies and caseecontrol/crosssectional studies. We investigated in total 20 unique outcomes, including 4 mortality outcomes (all-cause mortality [31], breast cancer mortality [32], cancer mortality [3,31], and cardiovascular disease mortality [3,31,32]); 7 cancer outcomes (colon cancer [33], colorectal cancer [33], esophageal adenocarcinoma [34], esophageal cancer [34], esophageal squamous cell carcinoma [34], ovarian cancer [35], and prostate cancer [36]); and 9 other outcomes (all fractures [37], coronary heart disease [38], Crohn's disease [39,40], frailty [41], hip fracture [37], hypertension [38], Parkinson's disease [42], T2DM [43,44], and ulcerative colitis [45]) (Table 1).…”
Section: Characteristics Of the Included Meta-analysesmentioning
confidence: 99%
“…We found that 42 (72.4%) meta-analyses included only prospective cohort studies, while 16 (27.6%) meta-analyses included either caseecontrol/cross-sectional studies or a combination of prospective cohort studies and caseecontrol/crosssectional studies. We investigated in total 20 unique outcomes, including 4 mortality outcomes (all-cause mortality [31], breast cancer mortality [32], cancer mortality [3,31], and cardiovascular disease mortality [3,31,32]); 7 cancer outcomes (colon cancer [33], colorectal cancer [33], esophageal adenocarcinoma [34], esophageal cancer [34], esophageal squamous cell carcinoma [34], ovarian cancer [35], and prostate cancer [36]); and 9 other outcomes (all fractures [37], coronary heart disease [38], Crohn's disease [39,40], frailty [41], hip fracture [37], hypertension [38], Parkinson's disease [42], T2DM [43,44], and ulcerative colitis [45]) (Table 1).…”
Section: Characteristics Of the Included Meta-analysesmentioning
confidence: 99%
“…A meta-analysis of 11 studies with 2,537 cases and 11,432 participants by Kong et al (2020) (63) found no association between overall dietary protein intake and esophageal cancer risk. Still, a sub-analysis revealed an increased risk for esophageal squamous cell carcinoma.…”
Section: Cancermentioning
confidence: 99%
“…Dietary protein intake can impact cancer risks depending on the type and amount of protein consumed [13][14][15]. The higher red meat consumption, as a source of dietary protein, is responsible for 3.21% of BC mortality [10].…”
Section: Introductionmentioning
confidence: 99%
“…The higher red meat consumption, as a source of dietary protein, is responsible for 3.21% of BC mortality [10]. It has been suggested that a high intake of protein could increase the risk of certain types of cancer, including prostate cancer, esophageal cell carcinoma, and colon cancer [13][14][15]. There are conflicting results from various studies.…”
Section: Introductionmentioning
confidence: 99%